Integrated spatial multi‐omics profiling of Fusobacterium nucleatum in breast cancer unveils its role in tumour microenvironment modulation and cancer progression - Feng Zhao; Rui An; Yilei Ma; Shaobo Yu; Yuzhen Gao; Yanzhong Wang; Haitao Yu; Xinyou Xie; Jun Zhang (Clinical and Translational Medicine)
Abstract Tumour‐associated microbiota are integral components of the tumour microenvironment (TME). However, previous studies on intratumoral microbiota primarily rely on bulk tissue analysis, which may obscure their spatial distribution and localized effects. In this study, we applied in situ spatial‐profiling technology to investigate the spatial distribution of intratumoral microbiota in breast cancer and their interactions with the local TME. Using 5R 16S rRNA gene sequencing and RNAscope FISH/CISH on patients’ tissue, we identified significant spatial heterogeneity in intratumoral microbiota, with Fusobacterium nucleatum (F. nucleatum) predominantly localized in tumour cell‐rich areas. GeoMx digital spatial profiling (DSP) revealed that regions colonized by F. nucleatum exhibit significant influence on the expression of RNAs and proteins involved in proliferation, migration and invasion. In vitro studies indicated that co‐culture with F. nucleatum significantly stimulates the proliferation and migration of breast cancer cells. Integrative spatial multi‐omics and co‐culture transcriptomic analyses highlighted the MAPK signalling pathways as key altered pathways. By intersecting these datasets, VEGFD and PAK1 emerged as critical upregulated proteins in F. nucleatum‐positive regions, showing strong positive correlations with MAPK pathway proteins. Moreover, the upregulation of VEGFD and PAK1 by F. nucleatum was confirmed in co‐culture experiments, and their knockdown significantly reduced F. nucleatum‐induced proliferation and migration. In conclusion, intratumoral microbiota in breast cancer exhibit significant spatial heterogeneity, with F. nucleatum colonization markedly altering tumour cell protein expression to promote progression and migration. These findings provide novel perspectives on the role of microbiota in breast cancer, identify potential therapeutic targets, and lay the foundation for future cancer treatments. Key points Intratumoral Fusobacterium nucleatum exhibits significant spatial heterogeneity within breast cancer tissues. F. nucleatum colonization alters the expression of key proteins involved in tumour progression and migration. The MAPK signalling pathway is a critical mediator of F. nucleatum‐induced breast cancer cell proliferation and migration. VEGFD and PAK1 are potential therapeutic targets to mitigate F. nucleatum‐induced tumour progression.